Sektor LULUCF v Sloveniji: obračunavanje, skladnost in obeti do leta 2030 The LULUCF sector in Slovenia: accounting, compliance and outlook to 2030 - Mali, Boštjan (Gozdarski vestnik, 2026)
Forest land is the most important category in the LULUCF sector, as it contributes most of the net greenhouse gas sinks. The period 2014–2018 was marked by natural disturbances, which caused the sector to shift from a net sink to a source of emissions, however data after 2018 indicate a gradual recovery of sinks. The average annual sink on managed forest land was just under –4,500 kt CO2 eq, while sinks on afforested land and grassland are declining. Accounting for the period 2021–2025 is carried out according to specific rules for each land category, with a key element being the technical correction of the forest reference level (FRL), which ensures consistency between FRL projections and national estimates. This correction is required due to changes in forest area and the use of different conversion factors for tree species, while other flexibility options are also available. The sector is estimated to have achieved a surplus of sinks for the period 2021–2024 and to comply with its commitment not to exceed emissions. In the period 2026–2030, Slovenia will report in accordance with the revised Regulation (EU) 2023/839, aiming to achieve a sink of –146 kt CO2 eq in 2030. The Commission may apply methodological adjustments to inventories to ensure data consistency, with the targets remaining unchanged. Based on the EU reference scenario and national projections, the LULUCF sector is expected to continue contributing to net sinks in the future.
Keywords: emisije toplogrednih plinov; forest land; FRL; gozdna zemljišča; greenhouse gas emissions; LULUCF; net sinks; neto ponori; sustainable forest management; technical correction; tehnični popravek; trajnostno gospodarjenje z gozdovi